Honduras recognizes CIAT's role in food system transformation. - Wiegel, Jennifer; Mosquera Echeverry, Erika Eliana (2024)
The Honduras Food System Profile (HFSP) — co-produced in 2020-2022 under Alliance leadership with inputs from key public-private stakeholders — provides an innovative, evidence-based overview of the current state and trends in the Honduran food system and highlights critical components needed for Honduran food-system sustainability. Both the HFSP and the Alliance’s Food-Systems Conceptual Framework underpinned introductory presentations at the Honduras Food Systems Dialogues preceding the United Nations Food Systems Summit (UNFSS) and Honduras’s Roadmap for Food Systems Transformation presented at UNFSS. In 2023, the Government of Honduras’ voluntary review of food systems transformation progress for the UNFSS Stocktaking Moment recognized the Roadmap and the HFSP as key achievements of na